On The New Russian Eastern Policy - A. V. Torkunov (Vestnik MGIMO-Universiteta, 2014)
The article analyses the new Eastern foreign policy of Russia, which has been developing since 2011, and the realization of various projects within this policy. The author posits that world is undergoing profound and dynamic changes, which boil down to two interconnected processes: 1) economic power shift towards Asia-Pacific region, which will define in the near future the shape of the world system; 2) shift of the main political, economic and military contradictions in world politics to this region. These core changes in world politics are also effected by trends in development of Russia and its near abroad. For more than a quarter of the century Russia has been pursuing a regional leadership in building among post-soviet states a mutual space for common interests open for other members of international community. This policy became known as "new Russian Eastern policy" or a policy of Eurasian integration. Its main goal is to establish Eurasian economic union by 2015 which will open boarders of the member states for unrestricted movement of goods, services, capital and workers within the emerging regional market with the total volume of 170-180 million people. Russian leaders look forward to discussing with their European partners prospects for merging Eurasian and European unions into a single economic space stretching from Lisbon to Vladivostok. Conceptually the strategy of Eurasian integration stems from a belief in unity of economic, cultural, civilizational interests of the Eurasian member states with state interests in Asia and Asia-Pacific. Realization of the new Eastern policy will be accompanied by the long awaited development of the Russian Eastern regions.